The Effect Of Work Motivation, Work Discipline, And Physical Work Environment On Performance Officers At The SME Cooperative Office Industry And Trade Medan City - Angellika Cindy; Muhammad Toyib Daulay (International Journal of Management, Economic and Accounting, 2025)
The purpose of this study is to analyze the influence of work motivation, work discipline, and physical work environment on employee performance at the Medan City Industrial and Trade SME Cooperative Office. This type of research is associative research with quantitative descriptive analysis, this research was carried out at the Medan City Industrial and Trade SME Cooperative Office on Jl. Gatot Subroto No.KM. .77, Lalang, Medan Sunggal District, Medan City, North Sumatra, This study was conducted on 81 employees of the Medan City Industrial and Trade SME Cooperative Office using saturated sampling techniques, the data analysis technique used in this study is multiple linear regression analysis, the results of this study are partially Motivation affects the performance of employees at the Cooperative Office, SMEs, Industry and Trade of Medan City This can be read from the score of t calculation (4.859) > t table (1.990) and the significance level of 0.000 < 0.05. The results of this study are partially disciplined and significantly affect the performance of employees at the Medan City Cooperatives, SMEs, Industry and Trade Office, this can be read from the score of t calculation (2.564) > t table (1.990) and the significance level of 0.012 < 0.05. The results of this study partially the Physical Work Environment does not affect the performance of Employees at the Medan City Cooperatives, SMEs, Industry and Trade Office, this can be read from the score of t calculation (0.707) < t table (1.990) and the significance level of 0.482 > 0.05. The independent variables consisting of Work Motivation (X1), Work Discipline (X2), and Physical Work Environment (X3) simultaneously have a significant effect on the performance of Employees at the Cooperatives, SMEs, Industry and Trade Office of Medan City.